The Robot is Present: Creative Approaches for Artistic Expression With Robots - Gomez Cubero, Carlos; Pekarik, Maros; Rizzo, Valeria; Jochum, Elizabeth (Frontiers in Robotics and AI, 2021)
There is growing interest in developing creative applications for robots, specifically in relation to social robots and other technologies that provide entertainment, companionship, or motivation. Identifying the hallmarks of human creativity and discerning how these processes might be replicated or assisted by robots remain open questions. Transdisciplinary collaborations between artists and engineers can offer insights into how robots might foster creativity for human artists and open up new pathways for designing interactive systems. This paper presents an exploratory research project centered on drawing with robots. Using an arts-led, practice-based methodology, we developed custom hardware and software tools to support collaborative drawing with an industrial robot. A team of artists and engineers collaborated over a six month period to investigate the creative potential of human-robot interaction. The exploratory project focused on identifying creative and collaborative processes in the visual arts, and later on developing tools and features that would allow robots to participate meaningfully in these processes. The outcomes include a custom interface for controlling and programming robot motion (EMCAR) and custom tools for replicating experimental techniques used in visual art. We report on the artistic and technical outcomes and identify key features of process-led (as opposed to outcome-led) approaches for designing collaborative and creative systems. We also consider the value of embodied and tangible interaction for artists working collaboratively with computational systems, which can lead to surprising and unexpected outcomes. Transdisciplinary research can help researchers uncover new approaches for designing interfaces for interacting with machines.